Analysis of Work Motivation, Work Discipline, Job Satisfaction and Job Loyalty to Employee Performance of PT. Matahari Department Store East Jakarta - Nadya Putri Camelie; Subur Karyatun; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze work motivation, work discipline, job satisfaction, and work loyalty on employee performance at PT Matahari Department Store, East Jakarta. In this study, researchers used data collection techniques through questionnaires distributed to respondents. This study uses primary data which is distributed to 100 respondents. The data analysis technique uses multiple linear regression analysis and uses the Statistical Product and Service solution (SPSS) program. The results of the multiple linear regression analysis show that the variables Work Motivation (X1), Work Discipline (X2), have no effect on the performance of employees at PT Matahari Department Store, East Jakarta. Meanwhile, Job Satisfaction (X3) and Job Loyalty (X4) have a positive and significant effect on Employee Performance at PT Matahari Department Store, East Jakarta. The results of this study are expected that the company is able to maintain and improve the performance of employees of PT. Matahari Department Store, East Jakarta.